Supplier Development and Performance of State Agencies in the Ministry of Education in Kenya - Nthusi, Jeremiah Kiio; Ismail, Noor; Thogori, Miriam; Ndeto, Charles K. (Integrasi Sains Media, 2025)
State agencies under the Ministry of Education play a pivotal role in delivering effective educational services, which are essential for a country’s economic development and citizens' quality of life. However, persistent poor performance in service delivery among these agencies has been reported. This study investigated the impact of supplier development on the performance of state agencies in Kenya’s Ministry of Education, guided by the Social Exchange Theory. Employing a descriptive-correlational research design, the study targeted 3,678 staff across eight state agencies under the Ministry, selecting a sample of 212 respondents using Nassiuma's Formula and purposive stratified sampling. Primary data was collected using structured questionnaires, and the analysis involved descriptive and inferential statistical methods for quantitative data, while thematic analysis was used for qualitative insights. The findings revealed inadequate implementation of supplier development practices in the state agencies, contributing to suboptimal performance in service delivery, cost efficiency, and customer satisfaction. The study concluded that supplier development significantly influences the performance of state agencies. Recommendations include prioritizing supplier development initiatives, such as capacity building and training, to align supplier capabilities with agency needs for improved service delivery.